Controllable 3D Porous Ni Current Collector Coupled with Surface Phosphorization Enhances Na Storage of Ni3S2 Nanosheet Arrays. Issue 8 (12th December 2021) - Fan, Xiaoyong; Sun, Ruibo; Zhu, Yongqiang; Zhang, Shuai; Gou, Lei; Lu, Li; Li, Donglin
Abstract: 3D porous Ni is fabricated via an easily scalable electroless plating method using a dynamic template formed through in‐situ hydrogen bubbles. The pore size in the range of several micrometers is controllable through adjusting the Ni 2+ depositing rate and hydrogen bubbles releasing rate. The Ni3 S2 nanosheet arrays anode is then grown on the unique 3D porous Ni current collector followed by subsequent surface phosphorization. The tremendous interconnected pores and rich voids between the Ni3 S2 nanosheet arrays cannot only provide rapid transferring channels for Na +, but also accommodate volumetric changes of the Ni3 S2 electrode during cycling, guaranteeing the integrity of the active material. In addition, the surface phosphorized layer enhances the electronic conductivity through providing an electron transport highway along the 3D Ni3 S2, NiP2 layer, and 3D porous Ni current collector, and simultaneously stabilizes the electrode/electrolyte interphase as a protecting layer. Because of these merits, the phosphorized 3D porous Ni3 S2 (3D P‐Ni3 S2 ) electrode is capable of delivering an ultra‐stable capacity of 387.5 mAh g −1 at 0.1 A g −1, and a high capacity retention of 85.3% even at a high current density of 1.6 A g −1 . Abstract : 3D porous Ni is fabricated via an easily scalable electroless plating method using a dynamic template formed through the in‐situ hydrogen bubbles, and its pore size is controllable in the range of several micrometers. The 3D porous Ni current collector coupled with surface phosphorization leads to ultra‐stable cyclability and an excellent high‐rate capacity of the Ni3 S2 electrode.